PENGARUH INSENTIF PERPAJAKAN AKIBAT COVID-19, PEMAHAMAN PERPAJAKAN, KESADARAN WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK DALAM MENYAMPAIKAN SURAT PEMBERITAHUAN TAHUNAN (STUDI PADA WAJIB PAJAK YANG TERDAFTAR DI KPP PRATAMA MALANG UTARA) - Zuli Alfina; Nur Diana (e_Jurnal Ilmiah Riset Akuntansi, 2021)
This study aims to find out the effect of tax incentives due to covid-19, understanding taxation, taxpayer awareness of taxpayer compliance in delivering annual notices. This research is quantitative research with correlational research type to test research hypothesis. The samples in this study were determined through a simple random sampling technique of 100 respondents. The results of this study showed that from the hypothesis test partially tax incentives due to covid-19 positively and significantly affect the compliance of taxpayers in delivering annual notices, understanding taxation has a positive and significant effect on taxpayer compliance in delivering annual notices, taxpayer awareness positively and significantly affects taxpayer compliance in delivering annual notices.Keywords: Tax incentives due to covid-19, Understanding taxation, Taxpayer awareness, Taxpayer compliance in delivering annual notices